2017
DOI: 10.2217/rme-2016-0094
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Adipose-Derived Stem Cells and Macrophages for Ischemic Skeletal Muscle Repair

Abstract: Aim: Progressive ischemia due to peripheral artery disease causes muscle damage and reduced strength of the lower extremities. Autologous cell therapy is an attractive treatment to restore perfusion and improve muscle function. Adipose-derived stem cells (ASCs) have therapeutic potential in tissue repair, including polarizing effects on macrophages (MPs). Materials & methods: Co-culture systems of ASCs and MPs were analyzed for gene and protein expression modifications in ASC-conditioned MPs. Co-transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…This has become even more relevant since recent studies showed that M1-polarized macrophages predominate in inflamed subcutaneous tissue of non-healing wounds [ 30 ]. On the contrary, ASC-cytokines induced an M2-like macrophage phenotype in vitro, and in vivo the beneficial effects of a combined macrophage/ASC treatment were demonstrated in a mouse model [ 31 ]. These findings would suggest a combined macrophages/ASC cell therapy also for non-healing wounds, such as ulcers and burn injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This has become even more relevant since recent studies showed that M1-polarized macrophages predominate in inflamed subcutaneous tissue of non-healing wounds [ 30 ]. On the contrary, ASC-cytokines induced an M2-like macrophage phenotype in vitro, and in vivo the beneficial effects of a combined macrophage/ASC treatment were demonstrated in a mouse model [ 31 ]. These findings would suggest a combined macrophages/ASC cell therapy also for non-healing wounds, such as ulcers and burn injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, they may affect the remodeling of the regenerating muscle and the maturation of muscle cells, perhaps by a direct effect of ASCs migrating to affected muscles as reported previously (Vieira et al, 2012). Thus, ASCs could directly act on muscle recovery and enhance muscle regeneration (Rodriguez et al, 2005;Rybalko et al, 2017). By immunostaining of human nuclear marker Ku80 (Koike et al, 1999;Allard et al, 2014), we addressed settlement of systemically applied ASCs in muscles (Supplementary Figure S5).…”
Section: Effects Of Ascs On De/regeneration Of Muscle and Nmjsmentioning
confidence: 91%
“…Generally, ADSCs are known to secrete multiple angiogenic growth factors, including vascular endothelial growth factor and platelet‐derived growth factor . Rybalko et al reported therapeutic potential of ADSCs in ischemic skeletal muscle models through growth factor secreted by cultured adipose tissue–derived stromal cells. Nakagami et al confirmed that ADSCs are directly involved in the development of vasculogenesis in the damaged site of ischemic limb.…”
Section: Discussionmentioning
confidence: 99%